Modelling the Australasian financial cycle: A Markov-Regime Switching Approach - Milan C. de Wet (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2021)
Purpose: The importance of the financial cycle has become a central point of consideration for policymakers since the 2007-08 financial crisis. This study aimed to construct and characterize the aggregate Australasian financial cycle. Design/methodology/approach: To construct the aggregate cycle, a dynamic factor model is employed, based on credit aggregates and aggregate property prices in Australia and New Zealand. To extract the aggregate Australasian financial cycle, the Christiano-Fitzgerald bandpass filter is implemented. Also, a Markov-Regime Switching Autoregressive model is employed to model, characterize and identify asymmetries in the aggregate Australasian financial cycle. Findings: The results indicate that Australian credit conditions are the prominent underlying driver of the aggregate Australasian financial cycle. The aggregate Australasian financial cycle exhibits a typical duration of 45 quarters, with expansions typically lasting 25 quarters and contractions lasting 20 quarters. Australasian financial cycles thus typically last longer than business cycles. The results also provide evidence that contractions in the aggregate Australasian financial cycle are typically shorter but harsher and more volatile than cyclical expansions, and that a level of linear persistence exists in the cycle. Research limitations/implications: A limitation of this study is that full data sets for all the variables that constitute the aggregate Australasian financial cycle is only available from 1978Q1. Therefore, the time horizon of the study starts at this point. However, given the long typical long duration of financial cycles, it would be ideal to have a time horizon of about 100 years. The implications of asymmetry in the aggregate cycle have several policy implications. Asymmetries might necessitate different policy strategies, as well as influence the timing of implementing policies during different financial cycle phases. The durational asymmetry in the aggregate financial cycle, whereby expansions in the aggregate financial cycle are typically longer than contractions, indicates that the employment of restrictive monetary and macroprudential policies should be implemented for longer periods than accommodative policies. Also, given that contractions in the aggregate financial cycle are steeper than expansions, policy response should be quicker and should be stronger with accommodative monetary policies once the aggregate financial cycle is in a contraction phase, relative to restrictive monetary policies during an expansion phase. Originality/value:The construction of a single aggregate measure that encapsulates the cyclical behaviour of a range of financial variables aids as a solution to simplify the study of aggregate financial cycles. In this light, this study contributes to the body of empirical literature on Australasian economic cycles by providing a single aggregate Australasian financial cycle measure that encapsulates the cyclical behaviour of several financial variables from two of the biggest economies in this region. This will provide policymakers with a single measure to consider the cyclical state of financial aggregates in Australasia. This study further contributes by establishing cyclical durations and identifying asymmetries in the cycle. Such an analysis aid in gaining a deeper understanding of the aggregate Australasian financial cycle and provide a means to improve the accuracy of predicting future movements in the financial cycle. This, in turn, could aid policymakers to manage fluctuations in the aggregate financial cycle and thereby reduce the potentially adverse effect of financial cycle fluctuations.
Keywords: G32; L25; L30; O34; 330; Financial cycle; dynamic factor model; MarkovSwitching; cyclical extraction; cyclical asymmetries